Pengembangan Pariwisata Konservasi Savana Propok, Lombok, Nusa Tenggara Barat - I Komang Deya Pradnyana; Agung Suryawan Wiranatha; I Gusti Ayu Oka Suryawardani (JURNAL MASTER PARIWISATA, 2022)
This research was conducted to design a conservation-based tourism development strategy in Savana Propok Sembalun, Lombok, West Nusa Tenggara. In developing Savana Propok Sembalun as conservation-based tourism, a general strategy (grand strategy) and alternative strategies are needed to develop all the existing potential, and support its development into a conservation tourism attraction that can benefit all parties, especially for the local community, so it is necessary to conduct research on (Conservation-Based Tourism) Savana Development Strategy in Propok Sembalun, Lombok, West Nusa Tenggara. This study was designed using a qualitative approach with the EFAS, IFAS, and SWOT matrix analysis methods. The data in this study were obtained through direct field observations and in-depth interviews with related parties. The results of this study refer to the internal and external environmental conditions of Savana Propok Sembalun, each of which are in a averange condition. Thus, the right alternative strategy to be applied at the next stage of development is to hold and maintain without changing the direction of the strategy that has been used. This alternative strategy emphasizes more on (1) Tourism Development Strategy, (2) Conservation Tourism Planning Strategy, (3) Conservation-Based Tourism Development Strategy, (4) Environmental Quality Improvement Strategy, (5) Human Resource Development Strategy, and (6) Tourist Attraction Promotion Strategy. Keywords: Development Strategy, Tourism, Conservation.